1993
DOI: 10.1136/gut.34.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of cow's milk beta-lactoglobulin to human serum after a milk load: a pilot study.

Abstract: A sensitive and specific enzyme linked immunosorbent assay (ELISA) was developed for the quantification of cow's milk 1-lactoglobulin in human serum. The assay had a sensitivity of 80 pg/ml (2 standard deviations from zero) and did not cross react significantly with any other tested milk proteins. The absorption of cow's milk 3-lactoglobulin and 1-lactoglobulin immunoglobulin G antibody levels after a milk load was investigated in eight healthy non-allergic individuals. There was a significant variation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Undegraded dietary antigens can penetrate the intestinal epithelial surface in immunologically signi®cant quantities in healthy and hypersensitive subjects (Lovegrove et al, 1993). Transferred antigens stimulate the production of speci®c antibodies which is, however, strictly controlled in healthy subjects (Challacombe & Tomasi, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Undegraded dietary antigens can penetrate the intestinal epithelial surface in immunologically signi®cant quantities in healthy and hypersensitive subjects (Lovegrove et al, 1993). Transferred antigens stimulate the production of speci®c antibodies which is, however, strictly controlled in healthy subjects (Challacombe & Tomasi, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was shown that albumin and b-lactoglobulin are transported through the intestinal mucosal barrier using luminal and intercellular routes. 23,24) Notably, the maximal antiangiogenic effect achieved with WSF was less than that with orally administered shark cartilage, which may have been due to a delayed effect as noted above. Oral PSC was given prior to, as well as after, bFGF pellet implantation, that resulted in an earlier antiangiogenic effect.…”
Section: )mentioning
confidence: 95%
“…It has been shown that albumin and b-lactoglobulin are transported through luminal or intercellular routes in small but significant quantities and that the rate of absorption is related to the amount of protein ingested and to some macromolecular characteristics such as molecular weight. 27,28) Conflicting Results in Studies with Shark Cartilage Although there is an increasing body of evidence showing that shark cartilage has potent antiangiogenic and antitumoral activities, some negativity can be found in the scientific literature concerning the usefulness of shark cartilage and derived compounds in the treatment of cancer and/or other angiogenesis-dependent diseases. This contrary viewpoint comes principally from two aspects: first, the lack of positive convincing results in clinical trials with the use of shark cartilage derived products, and second, the notion that cartilage-derived polypeptide factors are insufficiently absorbed through the intestinal wall after oral administration.…”
mentioning
confidence: 99%
“…As noted above, intact macromolecules, even insulin, can cross the intestinal barrier in a biologically active form and thus exert their pharmacological actions. 27,28) This absorption process may also occur with the active compounds of shark cartilage.…”
mentioning
confidence: 99%